2017
DOI: 10.1371/journal.pgen.1007098
|View full text |Cite
|
Sign up to set email alerts
|

Selection for long and short sleep duration in Drosophila melanogaster reveals the complex genetic network underlying natural variation in sleep

Abstract: Why do some individuals need more sleep than others? Forward mutagenesis screens in flies using engineered mutations have established a clear genetic component to sleep duration, revealing mutants that convey very long or short sleep. Whether such extreme long or short sleep could exist in natural populations was unknown. We applied artificial selection for high and low night sleep duration to an outbred population of Drosophila melanogaster for 13 generations. At the end of the selection procedure, night slee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
74
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(91 citation statements)
references
References 157 publications
16
74
1
Order By: Relevance
“…This view is supported by the observation that our study reveals a largely distinct genetic architecture from a previous sleep genomewide mapping study employing the DGRP lines [6]. Similarly, an artificial selection study initiated from DGRP strains with extreme sleep phenotypes observed little overlap at the polymorphism or gene level between loci identified in the GWAS and loci showing allele frequency changes following selection [22]. Nonetheless, we leveraged our mapping data, together with extant expression data, to point to three strong candidate genes, and our data suggest there is a link between natural variation in these genes and sleep phenotypes in flies.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…This view is supported by the observation that our study reveals a largely distinct genetic architecture from a previous sleep genomewide mapping study employing the DGRP lines [6]. Similarly, an artificial selection study initiated from DGRP strains with extreme sleep phenotypes observed little overlap at the polymorphism or gene level between loci identified in the GWAS and loci showing allele frequency changes following selection [22]. Nonetheless, we leveraged our mapping data, together with extant expression data, to point to three strong candidate genes, and our data suggest there is a link between natural variation in these genes and sleep phenotypes in flies.…”
Section: Resultssupporting
confidence: 83%
“…These heritability values are generally consistent with those obtained for the same traits in the DGRP inbred line GWAS panel [6] and demonstrate that considerable segregating variation for sleep and activity parameters exists within Drosophila populations. Indeed, recent work by Harbison et al [22] has leveraged this genetic variation to create long-and short-sleeping Drosophila lines via artificial selection and saw a rapid divergence in phenotype over a modest number of generations of selection.…”
Section: Extensive Genetic Variation For Sleep and Activity Traits Inmentioning
confidence: 99%
See 2 more Smart Citations
“…Likewise, artificially selected short-sleeping fruit flies have unaltered longevity (32). With flies joining pigeons in the list of animals surviving chronic sleep deprivation, the only solid evidence in favour of lethality upon sleep deprivation lays with the chronic sleep deprivation in rats using the disc-over-water system.…”
Section: Discussionmentioning
confidence: 99%